2017
DOI: 10.1186/s13075-017-1423-9
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of antibodies against common viruses associate with anti-citrullinated protein antibody-positive rheumatoid arthritis; implications for disease aetiology

Abstract: BackgroundInfection by common viruses has long been discussed in the aetiology of a number of autoimmune diseases, including rheumatoid arthritis (RA). However, studies investigating this hypothesis in RA show conflicting results. These studies often lack well-matched control populations, and many do not include data on autoantibodies, genetic risk factors and other environmental factors, which are known to contribute to disease only in subgroups of patients. In the present study, we have therefore examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…The immunological hypothesis with a defective immune control of infections at the early stage of RA is further reinforced by the observations that granulocytes are altered in their capacity to induce reactive oxygen species and that B cell evolution to memory B cells is impaired ( 12 , 31 , 32 ). Similarly, the recent report from the Swedish population-based Epidemiological Investigation of early RA (EIRA) supports an insufficient Ab response at the early stage of RA with lower anti-viral IgG levels for EBV, CMV, and parvovirus B19 ( 10 ). If true such a hypothesis would reinforce our observations that differences regarding infectious events concern not only qualitative and immune independent (prevalence) parameters but also immune controlled parameters (infectious events incidence and/or duration).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The immunological hypothesis with a defective immune control of infections at the early stage of RA is further reinforced by the observations that granulocytes are altered in their capacity to induce reactive oxygen species and that B cell evolution to memory B cells is impaired ( 12 , 31 , 32 ). Similarly, the recent report from the Swedish population-based Epidemiological Investigation of early RA (EIRA) supports an insufficient Ab response at the early stage of RA with lower anti-viral IgG levels for EBV, CMV, and parvovirus B19 ( 10 ). If true such a hypothesis would reinforce our observations that differences regarding infectious events concern not only qualitative and immune independent (prevalence) parameters but also immune controlled parameters (infectious events incidence and/or duration).…”
Section: Discussionmentioning
confidence: 87%
“…Altogether, these arguments support a causative role for infections in RA development. However, these findings regarding the link between Ab against infections and RA risk have not been replicated in large-scale cohorts and meta-analysis ( 8 , 9 ), leading instead to the proposition of an immunological hypothesis as one of the characteristics of RA patients in whom there is an inability of the immune system to properly control viral infections ( 10 ). This is in line with our recent findings, performed at the early stage of RA development in untreated subjects, showing both defects in the innate immune system and an elevated annual rate of infection events ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…A link between infectious agents and the development of Rheumatoid arthritis has been proposed and it has been shown that Rheumatoid arthritis patients have increased antibody titers against Epstein-Barr virus 80, 81 or cytomegalovirus 82 , as compared to healthy controls. Although in a few studies viral DNA and proteins have been detected in the synovium and joints of Rheumatoid arthritis patients, 83 these studies have not been confirmed and conclusions cannot be drawn from the current literature.…”
Section: Risk Of Infections In Rheumatoid Arthritis Patients and Effementioning
confidence: 99%
“…Nevertheless, other studies claim that no association between EBV infection and onset of RA is evident [ 110 , 125 , 126 ]. For example, findings by Sherina and colleagues, analyzing anti-viral antibodies in relation of ACPAs, smoking HLA-DRB1 alleles and clinical parameters, do not support the hypothesis of EBV involvement in RA onset [ 126 ]. These findings are supported by similar studies analyzing antibody levels to several viral proteins [ 110 ].…”
Section: Introductionmentioning
confidence: 99%